1997
DOI: 10.1016/s0013-4686(97)00189-8
|View full text |Cite
|
Sign up to set email alerts
|

An electrochemical active valve

Abstract: Abstract-Anovel electrochemical microactuator was developed, which operates as an active valve. The microactuator consists of an electrochemical cell and a membrane that deflects because of the pressure of oxygen gas generated by electrolysis. Relatively large pressures (up to tens of bars) can be reached with only low energy consumption (in the PW range). In a first prototype a Cu/aq. 1 M CuSOdPt system was used in an electrochemical cell with dimensions 2 x 2 x 1 mm3, fabricated with silicon micromachining a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 7 publications
(9 reference statements)
0
27
0
Order By: Relevance
“…The technology of handling nano-and picoliter volumes of fluids started in the 1980s (Whitesides, 2006) and over the years a variety of different methods and system have been reported for fluidic actuation and handling (Sackmann et al, 2014). The most commonly used fluid handling systems for cell cultures are based on either pressure driven or passive driven flow profiles using syringe- (Stevens et al, 2008;Chin et al, 2011;Song et al, 2014) and electrochemical pumps (Neagu, 1996;Neagu et al, 1997) as well as gravimetrically (Kim et al, 2008b) driven flow systems. Overall, the high response time (few seconds) and a very robust and long term reliability and consistency (together with relatively low power consumption) made syringe pump driven microfluidic systems one of the most commonly used for microfluidic cell cultures to date.…”
Section: Liquid Handling Systems For Microfluidic Cell Culturesmentioning
confidence: 99%
“…The technology of handling nano-and picoliter volumes of fluids started in the 1980s (Whitesides, 2006) and over the years a variety of different methods and system have been reported for fluidic actuation and handling (Sackmann et al, 2014). The most commonly used fluid handling systems for cell cultures are based on either pressure driven or passive driven flow profiles using syringe- (Stevens et al, 2008;Chin et al, 2011;Song et al, 2014) and electrochemical pumps (Neagu, 1996;Neagu et al, 1997) as well as gravimetrically (Kim et al, 2008b) driven flow systems. Overall, the high response time (few seconds) and a very robust and long term reliability and consistency (together with relatively low power consumption) made syringe pump driven microfluidic systems one of the most commonly used for microfluidic cell cultures to date.…”
Section: Liquid Handling Systems For Microfluidic Cell Culturesmentioning
confidence: 99%
“…To this end, two of the representative approaches reported in the literature are boiling water using a microheater [86,87] and causing electrolysis on a microfabricated electrode [86,[88][89][90][91][92][93][94]. In both cases, devices that pump a solution out of a solution are easily formed.…”
Section: Microfluidic Transport Based On the Volume Change Of Bubblesmentioning
confidence: 99%
“…The electrochemical (ECM) actuation is a very attractive one in microfluidic applications because it permits very simple structural designs (Böhm et al 2000). In recent years, many research efforts have been reported on using ECM actuation as an alternative to other high voltage or power consumption actuators such as electroosmosis (Neagu et al 1997;Stanczyk et al 2000;Xie et al 2004;Yoneyama 2002, 2003). The ECM actuation is based on reversible ECM reactions that enable gas evolution (gas bubble expansion) and reduction in the aqueous electrolyte solution.…”
Section: Introductionmentioning
confidence: 99%